Effect of Palate Re-Repairs and Hynes Pharyngoplasties on Pediatric Airways: An Analysis of Preoperative and Postoperative Cardiorespiratory Sleep Studies. (May 2013) - Mehendale, Felicity V.; Lane, Rod; Laverty, Aidan; Dinwiddie, Robert; Sommerlad, Brian C.
Objectives: To determine whether Sommerlad palate re-repairs and Hynes pharyngoplasties cause obstructive sleep apnea/hypopnea or increased upper airway resistance. Design: Prospective before-and-after study. Setting: Tertiary cleft unit. Patients: A total of 44 patients undergoing a Sommerlad palate re-repair or a Hynes pharyngoplasty. Interventions: Preoperative and postoperative multichannel cardiorespiratory sleep studies. Main Outcome Measures: The main outcome measures were mean arterial oxygen saturation, desaturation index, percentage of time spent with arterial oxygen saturation <90%, mean pulse rate, number of pulse rate rises (arousals) per hour, inspiratory effort derived from pulse transit time, pulse transit time arousals, and snoring. Results: No patient in either group required intervention for airway obstruction or obstructive sleep apnea/hypopnea. Re-repairs caused no significant change in any parameter. Hynes caused an increase in inspiratory effort ( P = .04) and obstructive sleep apnea/hypopnea grading ( P = .002). All other parameters showed no significant deterioration. No patient developed more than mild/ moderate obstructive sleep apnea/hypopnea. Snoring and arterial oxygen saturation levels were not reliable indicators of increased inspiratory effort. Conclusions: A palate re-repair had no significant adverse effect on the airway. A Hynes, in patients with optimized velar function, caused a significant increase in inspiratory effort and obstructive sleep apnea/hypopnea grade. However, compared with studies on midline flaps and on sphincter pharyngoplasties, a Hynes appears to be less obstructive. Failure to study changes in inspiratory effort in patients undergoing velopharyngeal incompetence surgery may underestimate the obstructive effect of pharyngoplasties.